MiR-429 prohibited NF-κB signalling to alleviate contrast-induced acute kidney injury via targeting PDCD4 - Hui-Min Niu; Li-Qin Guo; Yan-Hong Qiao; Hai-Yan Jiao (Taylor & Francis Group, 2021)
MiR-429 was reported to be downregulated in contrast-induced acute kidney injury (CI-AKI). However, whether miR-429 is functionally relevant with CI-AKI needs further investigation. Human renal tubular epithelial cell (HK-2) cells were stimulated with contrast media iodixanol to establish in vitro CI-AKI model. Cell Counting Kit-8 (CCK-8) was applied to access cell viability. Flow cytometry was performed to determine apoptosis. Quantitative real-time polymerase chain reaction (qRT-PCR) was applied to evaluate level of programmed cell death 4 (PDCD4) mRNA and miR-429 while western blot was applied to evaluate level of proteins including PDCD4, B-cell leukaemia/lymphoma 2 (Bcl-2), BCL2-associated X protein (Bax), cleaved caspase 3, cleaved caspase 9, p65, phosphorylated p65. Dual luciferase assay was used to validate miR-429 targeting PDCD4. MiR-429 was downregulated whereas PDCD4 was upregulated in contrast media iodixanol-stimulated HK-2 cells. MiR-429 overexpression elevated cell viability and attenuated cell apoptosis. Moreover, the activation of nuclear factor kappa-B (NF-κB) signalling was suppressed after miR-429 overexpression, while PDCD4 overexpression reversed these effects. MiR-429 directly targeted PDCD4 and negatively regulated its expression. CI-AKI induced NF-κB signalling activation and PDCD4 overexpression further promoted NF-κB signalling activation. However, the treatment of BAY11-7082 reversed above results. Overexpression of miR-429 attenuated apoptosis and elevated cell viability in a CI-AKI cell model via targeting PDCD4 and thus restraining NF-κB signalling.